Karo Traditional House, Siwaluh Jabu in Dokan Village and its role in North Sumatra Tourism - Aynen Kresensia Br Sembiring; Rani Evilona Purba; Jenny D. Manurung; Nael Simarmata; Meisuri Meisuri (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
The Siwaluh Jabu traditional house in Dokan village is a historical relic of the Karo tribe, which still stands today. The Siwaluh jabu traditional house in Dokan village is a cultural tourist attraction that is often visited by tourists. Therefore, the purpose of this study is to review the condition of the traditional house and the role of the Siwaluh jabu traditional house in Dokan village on tourism in North Sumatra. The method used in this research is a qualitative research method which collects data from interviews conducted and information from journals and books. From the research that has been done, it is found that the condition of the traditional house of Siwaluh Jabu in Dokan village is still good but one of the traditional houses has been damaged and is no longer occupied. The Siwaluh Jabu traditional house in Dokan village also has an important impact on tourism in North Sumatra.